Value of gel filtration on Sephadex G-200 in the analysis of blood group antibodies. Issue 6 (November 1968) - Stratton, F.; Smith, D. S.; Rawlinson, V. I.
Abstract : Analysis of blood group antibodies on Sephadex G-200 columns is described. The position of blood group antibodies when whole serum containing them is subjected to gel filtration is studied and compared with the position of the γ-globulins and of standard blood group antibodies. The technique on its own cannot be used to identify the immunoglobulin nature of the antibody but is very useful when employed in conjunction with the antiglobulin test using specific antisera and with other methods. The technique is rapid, simple, and reliable.